2022
DOI: 10.2147/jpr.s357076
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Failed Lateral Sacroiliac Joint Fusion with a Novel Posterior Sacroiliac Fusion Device: Diagnostic Approach, Surgical Technique, and Multicenter Case Series

Abstract: Background Studies have found that up to one-third of patients with LBP have sacroiliac joint (SIJ) dysfunction as a contributing cause. Historically, the management of SIJ dysfunction has been plagued by ineffectiveness or significant morbidity. In 2008, minimally invasive lateral SIJ fusion was developed. While this procedure is a safe and effective treatment, there is still a significant proportion of patients who will not experience therapeutic success. There is a paucity of data in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Sayed et al reported on the use of a minimally invasive posterior approach SIJF device (Linq [PainTeq, Tampa, FL, USA]) as a salvage of failed lateral SIJF in 7 patients. 35 The authors reported a mean NPRS improvement from 8 to 2 at final follow-up. Details regarding the indication for surgery were not included, and there was no formal evaluation of radiographic fusion prior to or after the revision procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Sayed et al reported on the use of a minimally invasive posterior approach SIJF device (Linq [PainTeq, Tampa, FL, USA]) as a salvage of failed lateral SIJF in 7 patients. 35 The authors reported a mean NPRS improvement from 8 to 2 at final follow-up. Details regarding the indication for surgery were not included, and there was no formal evaluation of radiographic fusion prior to or after the revision procedure.…”
Section: Discussionmentioning
confidence: 92%
“…However, investigators of this posterior approach have recently reported efficacies ranging from 66.5 to 76.5% [ 36 , 37 ]. Investigators have also reported in a multicenter case series, in which the posterior intra-articular technique (LinQ) was utilized as a salvage therapy for the lateral trans-articular technique (iFuse) patients who did not show pain improvement and fusion after 20 ± 8 months postoperation [ 38 ]. The investigators reported 77 ± 11% reduction in pain scores upon salvage therapy using the posterior intra-articular technique (LinQ) in all patients after 10 ± 6 months postoperation with evidence of bony bridging.…”
Section: Discussionmentioning
confidence: 99%
“…), and pain-tolerant walking distance by 55% (87 ± 267 steps to 135 ± 374 steps) I-C Sarkar, 2022 157 Retrospective, observational SI-LOK RIALTO Lateral vs Posterolateral 43 VAS, fusion rate Lateral versus posterolateral approach using robotic guidance versus Stealth Navigation System. Mean baseline VAS score decreased from 7.52 ± 1.3 to 1.43 ± 1.22; SIJ fusion rate was 61% at 6 months, 96.4% at 12 months, and 100% at 18 months I-C Sayed, 2022 158 Retrospective, observational LINQ Posterior 7 NRS, opioid use, fusion rate Subjects who failed fusion with a lateral approach underwent re-surgery with a posterior approach. The mean NRS improvement following posterior fusion was 80%; opioid use decreased with median morphine milliequivalents 20 pre-procedure and 0 post-procedure I-C Soliman, 2022 159 Retrospective, observational iFuse Lateral 33 VAS, ODI Mean VAS was 68.9 at baseline and decreased to 53.1; similarly showed a significant improvement postoperatively I-C Wessell, 2022a 160 Retrospective, observational iFuse Lateral 45 VAS, ODI, opioid use, DSIJQ No change in opioid use from baseline.…”
Section: Methodsmentioning
confidence: 99%
“…21,140 In a combined cohort of four studies involving 237 subjects who underwent posterior approach sacroiliac fusion, there were no serious adverse events reported, including no implant breakage, bone fracture, infection, bleeding requiring surgery, viscous perforation, but only one device migration. [72][73][74]158 Rajpal et al reported two hematomas and one infection on a cohort of 24 subjects. 135 Posterior sacroiliac fusion approach appears to have a significantly lower safety risk profile due to avoidance of critical neurovascular structures that can be encountered with lateral and posterolateral approaches.…”
Section: Summary Of Safety In Sij Fusionmentioning
confidence: 99%